'It was maendeleo that removed them': disturbing burials and reciprocal knowledge production in a context of collaborative archaeology. (June 2015) - Straight, Bilinda; Lane, Paul J.; Hilton, Charles E.; Letua, Musa
Abstract : Recent decades have witnessed a growth in approaches to research and writing across anthropology's four fields that emphasize the need to respect alternative narratives and constructions of history, and to engage with anthropology's 'publics'. These developments have generated more ethically responsible research and more inclusive writing practices. Nevertheless, the actual doing of cross‐cultural collaboration and knowledge production remains a challenge. In this three‐field (cultural, biological, and archaeological anthropology) study, we aim to capture, in writing, a process of collaborative fieldwork with Samburu pastoralists in northern Kenya that experimentally integrated ethnographic self‐scrutiny with a bio‐archaeological excavation involving human remains. In the process, we highlight the reciprocal knowledge production that this cross‐subdisciplinary, transcultural fieldwork produced.